The Role of Religious Leaders as Opinion Leaders in Government Communications Related to COVID-19 - Syarifah Kusumadewi Kinanggi; Muh. Akbar; Muhammad Farid (GoAcademica Research & Publishing, 2022)
Covid 19, it is undeniable that it has had a bad impact on people's lives, both in the health aspect, as well as in the political, economic, social, etc. This made the government then issue several handling policies, including: Implementing restrictions on community activities, implementing health protocols, including various rules in the order of religious life, one of which is an appeal to carry out worship at home. So that people can immediately know and obey these rules, of course we need an appropriate communication strategy by paying attention to the role of an opinion leader. Bulukumba Regency, South Sulawesi Province, which is the location of this research, is an area that has regulations on religion. Therefore, a religious figure can be said to be an opinion leader who has a strategic position, especially in communicating government policies related to Covid 19 on religious issues. This is in line with the two-step model of communication flow, both in the pattern of face-to-face communication and mass communication, which introduced the concept of opinion leader. This research method is descriptive qualitative with the aim of providing an overview of the role of religious leaders in government communication. Through the interview process with the Chairperson of the Indonesian Ulema Council and the Young Dai of Bulukumba Regency, it is known that religious leaders have a role in government communication in Bulukumba Regency, through direct da'wah or using digital media. Furthermore, of course the results of this research are expected to be an input for the government, in considering and determining opinion leaders on other issues.